Perioperative considerations for elective surgical patients following the COVID-19 pandemic. (2nd April 2022) - Patel, Jason; Singh, Manpreet
Abstract : COVID-19 has had a significant impact on patient health and the delivery of healthcare within the UK. This article highlights perioperative considerations as elective work moves back to pre-pandemic levels.